Mononuclear vs. binuclear carboxylates of copper(II) with 2, 2′‐bipyridine: Synthesis, characterization, structural description, and properties. Issue 12 (16th May 2019) - Iqbal, Muhammad; Ali, Saqib; Sohail, Manzar; Tahir, Muhammad N.; Anderson, Paul A.
Abstract: Two new copper(II) carboxylate complexes with 2, 2′‐bipyridine and para ‐nitrophenyl acetate (complex 1 ) and phenyl acetate (complex 2 ) have been synthesized; isolated in quantitative yield; and characterized using fourier‐transform infrared spectroscopy (FT‐IR), electron paramagnetic resonance, absorption spectroscopy, electrochemistry, and powder and single crystal X‐ray diffraction (XRD) techniques. Being mononuclear, the geometry around copper in complex 1 is a Jahn–Teller distorted octahedral, while complex 2 is binuclear with slightly distorted square pyramidal geometry around both copper ions. Powder XRD indicated several peaks in spectra of both complexes, which coincided with their theoretical spectra. FT‐IR results of the carboxylate stretching frequency were in accordance with the single crystal structure data. Electron paramagnetic resonance spectra of complexes 1 and 2 yielded g┴ values of 2.06161 and 2.24623 and 1.94959, respectively, indicating a localized electron in b1 ( d x 2 – y 2 ‐orbital). Ultra‐violet (UV)–visible spectroscopy and electrochemistry helped in characterization, as well as in deoxyribonucleic acid (DNA)‐binding ability of the complexes, yielding DNA‐binding constant values = 1.351 × 10 4 and 1.361 × 10 4 and 1.820 × 10 4 and 2.426 × 10 4  M −1, respectively, for complexes 1 and 2 . The complexes demonstrate good biological potential. Abstract : This work contains two structurally as well as biologically important mononuclear and binuclear complexes of copper with carboxylate ligands. Their structures have been mutually compared and their biological relevance manifested through various techniques.